Sistem Informasi Pencatatan Penerimaan dan Pengeluaran Stationary (SIPEPES) pada PT. X menggunakan Metode RAD dan UML - Nurlani, Lani; Martha Pratiwi, Devi; Abdul Rosid, Usep (Jurnal Sistem Informasi Galuh, 2023)
Office stationery (ATK) is a tool needed to support work and activities carried out in a company, the availability of ATK is handled by the General Affair (GA) Department. The difficulty that the GA Department has is recording each department's expenses from the bill forms provided, where the forms are sometimes not well organized and data collection is difficult to do one by one with several departments and many requests. In addition, purchases made by the purchasing department do not come all at once but gradually, so the GA Department must check requests that have not been purchased so that they can confirm. Therefore we need a system that can store and display all the information needed by the GA Department to support its activities in providing ATK. Information System for Recording Receipt and Issue of Stationary (SIPEPES) is built on a website basis with the Laravel framework and MySQL database using RAD software development method and UML as modeling. The results of this study are a system that can be used to record and monitor incoming and outgoing ATK at the company.